Sharia Economic Empowerment Efforts Through Koperasi Wanita Srikandi, Kelurahan Sidokerto, Kecamatan Buduran, Sidoarjo - Hersa, Hersa Farida Qoriani (Journal of Islamic Economics Perspectives, 2020)
The purpose of this research is to analyze the role of Koperasi wanita in efforts to empower women and empower the Islamic economy (especially mothers around the Koperasi wanita, Sidokerto, Kecamatan Buduran, Sidoarjo), the welfare conditions of members of koperasi Wanita, and the potential of Koperasi Wanita the future. The study was conducted at the Koperasi Wanita "Srikandi" in Sidokerto, Buduran, Sidoarjo. This research is qualitative and uses data collection techniques through interviews, observation and documentation. This study uses a qualitative approach because this study intends to find, understand, explain and obtain a picture of the role of the Koperasi Wanita "Srikandi" in increasing the incomes of members, especially community mothers around the Koperasi Wanita in Sidokerto, Buduran, Sidoarjo. The determination of informants is based on design samples to be able to represent all members of the Koperasi Wanita "Srikandi", then determined 15 respondents, namely 10 respondents from members and 5 respondents from the management of the Koperasi Wanita "Srikandi" After that an analysis of income through the average amount of income per year during the last five years, starting from 2013 to 2018. From the results of the study showed that the Koperasi Wanita "Srikandi" has a positive role in increasing the income of members and its existence benefits the members. Women apparently have an active role in the economy, an optimal potential empowerment towards productivity, so that they are able to achieve economic prosperity through cooperative activities. Women's participation through cooperatives is proven to have helped the family economy. This can be seen from the analysis of respondents' income and statements from respondents directly. From the statement given by each respondent that the respondents felt that the existence of the Koperasi Wanita Srikandi especially the Savings and Loans Unit and special training for members played an important role in business capital to keep going and even more advanced businesses. Although there are many financial institutions in the village of Sidokerto, Buduran , Sidoarjo, the respondents feel it is still more profitable to be a customer and a member of the Koperasi Wanita "Srikandi". In addition respondents also felt the benefits of having business units managed by the Koperasi Wanita "Srikandi" because they were able to meet the needs of members so that the Koperasi Wanita "Srikandi" gained the trust of the members. The trust of members is certainly responded by the Koperasi Wanita "Srikandi" by doing the best service so that members feel comfortable and prosperous.